Review of Benefits of Breast Feeding and other milks. - Narang, Ritu; Sharma, Nikhil (International Research Journal of Ayurveda & Yoga, 2020)
In Ayurveda the word used for the babies who drink only milk is “ ksheerap” and the one who drinks milk and eats solids is called as “ksheer-annad”. According to different authors, the age group of ksheerap and Ksheer-annad is different. Since the baby is only fed with milk initially, it becomes a prime issue as to what kind of milk must be given. Amongst the all, the mother’s milk is considered as the best, but here in this article the importance of mothers milk along with its substitute have been mentioned.